Design and Implementation: JavaFX Face Detection with Scene Builder and Netbeans IDE - Syefrida Yulina (International ABEC, 2021)
JavaFX face detection is an application widely used to detect and recognize faces in digital images. One of the challenging problems in the image processing is how to develop and design an automatic face recognition application using JavaFX technology. JavaFX is a library of Java that is used to build rich internet applications (RIA) which can run across several platforms such as Desktops, Mobile Devices, TVs, Tablets, etc. Design and implementation of this application applies the concept of model-view-controller using framework Scene Builder and Netbeans IDE. Scene Builder is used as a tool to add components of GUI in the view that can produce document called FXML. Netbeans IDE is an integrated development environment for FXML document editing and maintaining the connection between view and controller. In this research stages of creating JavaFX Face Detection application are started with requirements identification, followed by design of UI components in Scene Graph, integration of the scene builder panels, and then making controller